INFESTASI EKTOPARASIT PADA IKAN LELE DUMBO (Clarias gariepinus) YANG DIBUDIDAYA DI DESA TUMPOK TEUNGOH KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE - Winaruddin Winaruddin; Rusli Rusli; Khairul Razi (JESBIO : Jurnal Edukasi dan Sains Biologi, 2015)
The study was conducted to determine and identify ectoparasites of Clarias gariepinus from earthen ponds, Banda Sakti – Lhokseumawe. Ectoparasites examination carried out by the method of smear preparations from mucus scrapings body and gills of fish. Thereafter, the scraped samples of mucus together with the tissues were placed on a Petri-dish containing  of 0.9% saline solution and stirred using a mounted pin. Some drops of the mixed solution were collected using dropper, placed on a clean slide. The smears were fixed in methanol and stained with 5% Giemsa solution. Smears were then examined under microscope. Of the total number examined, 20 (40%) were infected with ectoparasites ( Trichodina sp. 20%. and Ichtyophthirius multifiliis 20%). Key words: ectoparasites, Trichodina sp., Ichtyophthirius multifiliis, “dumbo” catfish, Lhokseumawe